Study on combining ability and heterosis of maize inbred lines through line × tester method (Bangladesh Journal of Agricultural Research, 2026)
Eleven inbred lines were crossed with two testers in a Line × Tester mating design and the resulting twenty-two crosses along with the lines, testers and two checks BARI Hybrid Maize-9 (BHM-9) and 981 were evaluated during rabi season, 2013-14 in an alpha lattice design with two replications, for grain yield and its components to estimate the general combining ability (GCA) and specific combining ability (SCA) effects and heterosis. The analysis of variance (ANOVA) was found significant for most of the characters studied among the genotypes indicating greater diversity in the parental lines of the traits.  Parents with good GCA for yield, E21 and BIL51(1), for 1000 grain weight, line E21 and for grains/ear, BIL72 and BIL51(1) could be used in hybridization program as donor. Heterosis was noticed - 44.92 to 13.02% among the cross combinations.  However, three crosses BIL51(1) × BIL28, E21 × BIL95 and E04 × BIL95 were found promising considering SCA effect and could be utilized for enhancing hybrid production.Bangladesh J. Agril. Res. 48(1): 69-78, March 2023